Analisis Implementasi Proses Seleksi dan Rekrutmen pada PT XYZ - Angela Yang; Yuli Indah Fajar Dini (STIE Amkop Makassar, 2024)
As an archipelagic region strategically located along local and international maritime routes, Batam city holds significant potential for the development of its maritime industry. PT XYZ is one of the companies in Batam that operates within maritime transportation sector. With more than 55 employees, this company requires effective human resource management to seek, select and recruit qualified candidates who can contribute to company’s progress. However, PT XYZ faces challenges in acquiring quality candidates due to a lack of strategies and comprehensive assessment. This issue then adversely affects the quality and capabilities of the recruited workforce and overall productivity. To address these challenges, this project aims to develop a more effective selection and recruitment system utilizing data obtained through observation and documentation. This project consists of three stages, (1)preparation, (2)implementation and (3)evaluation and reporting, spanning from September 20th to December 20th, 2023. Project’s deliverables include a comprehensive selection and recruitment system, including designing a recruitment and assessment forms. It is expected that PT XYZ, particularly the human resource department, will utilize the developed system and enhance communication with prospective candidates in future recruitment process, thereby improving the effectiveness and efficiency of their practices.